PEMBERDAYAAN MASYARAKAT MELALUI PENDAMPINGAN PEMBUATAN SERTIFIKASI HALAL PRODUK UMKM DI DUSUN KEMPUL - Syara Aulia Shofa; Ahmad Muhibin; Ervina Rahmadila; Nur Kholidah (khidmatan, 2025)
Halal certification is a vital instrument for ensuring product wholesomeness and safety, while also serving as a crucial added value in enhancing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs). Nevertheless, micro-business actors frequently face obstacles such as limited understanding of BPJPH regulations, low digital literacy, and minimal access to technical assistance. This community service activity aims to provide education and direct assistance to business actors in Kempul Hamlet regarding understanding procedures, preparing documents, and submitting applications for Halal certification. The implementation method utilized the Participatory Action Research (PAR) approach, involving intensive training sessions, consultation, and direct assistance. The activity took place from February 17 to March 29, 2025. The results indicate that the assistance successfully helped producers understand certification requirements, ensured their products complied with applicable standards, and successfully assisted the MSMEs in submitting applications and commencing the implementation of the Halal Assurance System (SJH) in accordance with the Halal Product Guarantee Law (UU JPH).